First record for the flora of Italy and lectotypification of the name Linum elegans (Linaceae) - Wagensommer, Robert P.; Bartolucci, Fabrizio; Fiorentino, Michele; Licht, Wolfgang; Peccenini, Simonetta; Perrino, Enrico V.; Venanzoni, Roberto (Phytotaxa, 2017)
Linum elegans has been detected in calcareous rocky garrigues on the Gargano promontory (Apulia, SE-Italy), representing the first record for the Italian flora and the first one outside the Balkan Peninsula. The geographical disjunction may provide evidence for past amphi-Adriatic/amphi-Ionic terrestrial connections. The population found was ascribed to L. campanulatum in the past. As a consequence, a comparison between these two species is undertaken. Furthermore, the name L. elegans is here lectotypified on a specimen preserved at G, and the IUCN assessment of the species in Italy is briefly discussed.